Bentuk Penyajian Tari Mopotilro dalam Acara HUT PEREDAM di Kecamatan Bolaang Uki Kabupaten Bolaang Mongondow Selatan - Nurhikmah Jum'a Laselo; Riana Diah Sitharesmi; La Ode Karlan; Nurlia Djafar; Trubus Semiaji (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Mopotilro Dance is a traditional dance originating from South Bolaang Mongondow Regency that functions as a welcoming dance for guests in customary ceremonies. Academically, this dance has not yet been examined in depth. Therefore, this article aims to investigate the Mopotilro Dance from the perspective of its performance structure, particularly as presented at the anniversary celebration of the Persatuan Relawan Muda Molibagu (PEREDAM) community. The research focuses on several aspects of the dance presentation, including: (1) movement, (2) number of dancers, (3) makeup and costume, (4) musical accompaniment, (5) floor patterns, (6) properties used, and (7) performance space. This study employs a qualitative research method with data collection techniques consisting of observation, interviews, and documentation, which are used to describe the data and draw conclusions. The results indicate that the presentation of the Mopotilro Dance at the PEREDAM anniversary event is not found in other occasions. This condition suggests that public understanding of the Mopotilro Dance as part of local cultural heritage remains limited. The lack of academic studies on the performance structure of the Mopotilro Dance is one of the factors contributing to its rare appearance in various events.